The Effectiveness of Clove Leaf Extract (Syzygium Aromaticum) in Cleaning Smear Layer in Tooth Root Canals - Nur Asmah; Syamsiah Syam; Sarahfin Aslan; Widya Lestari; Resky Masyandah Masya (TALENTA, 2026)
The target of root canal treatment is to eliminate infected pulp tissue and preserve tooth function. Instrumentation produces a smear layer composed of organic and inorganic debris, which may promote microbial colonization and reduce sealer adhesion. Ethylene diamine tetra acetic acid (EDTA) 17% is widely used for smear layer removal but may cause periapical tissue toxicity, suggesting the need for safer natural alternatives. Clove leaf extract (Syzygium aromaticum) contains bioactive compounds such as flavonoids, phenolics, saponins, steroids, and alkaloids that may aid in smear layer removal. Therefore, this study aimed to evaluate the effectiveness of clove leaf extract in removing the smear layer from root canals. The extract was prepared using the maceration method and tested at concentrations of 10%, 15%, and 20%, with 17% EDTA used as the control group. The smear layer cleanliness was evaluated with a Scanning Electron Microscope (SEM), and data were analyzed using the Mann–Whitney test. Statistical analysis showed no significant difference between the 20% clove leaf extract group and the 17% EDTA group (p > 0.05). The 20% concentration showed comparable effectiveness to 17% EDTA in removing the smear layer from root canals.